Mastering AutoCAD 2010 and AutoCAD LT 2010 - Omura, George (Serious skills., 2009)
Turn Ideas into Reality with the New Free-Form 3D Design ToolOrganize Drawing Information with LayersTrack Your Projects with the Sheet Set Manager Annotate, Secure, and Authenticate FilesPrint in 3D, Publish Drawings over the Internet, or eTransmit Your FilesThe World's Bestselling AutoCAD Resource Fully Updated for 2010. There's a reason why Mastering AutoCAD is so popular year after year. Loaded with concise explanations, step-by-step instructions, and hands-on projects, this comprehensive reference and tutorial from award-winning author George Omura has everything you need to become an AutoCAD expert. If you're new to AutoCAD, the tutorials will help you build your skills right away. If you're an AutoCAD veteran, Omura's in-depth explanations of the latest features, including the exciting new free-form 3D design tool and new parametric capability, will turn you into an AutoCAD pro. Whatever your experience level and however you use AutoCAD, you'll refer to this indispensable reference again and again. Coverage includes:Effectively using hatches, fields, and tablesManipulating dynamic blocks and attributesLinking drawings to databases and spreadsheetsRendering realistic interior views with natural lightingGiving a hand-drawn look to 3D viewsPresenting 3D models with cutaway and x-ray viewsImporting PDF documents as drawing backgroundsExploring parametric modeling with geometric constraintsFeatured on the DvdFind all of the project files for the book's exercises, Autodesk-created videos highlighting new features in AutoCAD 2010, 20 video tutorials, a trial version of AutoCAD 2010, a searchable PDF of the book, and additional tools and utilities.